Expressing Condition in English and in Polish. - Polanska, Irena (Jagiellonian University Press, 2006)
The purpose of this work is to give a detailed description of the ways of expressing condition in English and in Polish, and to present similarities and differences between the forms in these two languages. In order to do that I will analyse those aspects of conditional sentences that contribute to their interpretation and I will try to present how the form of conditionals influences the meaning they convey. Thus, the description will cover the role of the component clauses and conjunctions, verb forms and function words, but also clause and word order.